1993
DOI: 10.1212/wnl.43.10.1966
|View full text |Cite
|
Sign up to set email alerts
|

Frontal lobe epilepsy

Abstract: We evaluated ictal 99mtechnetium hexamethyl propylene-amine-oxime single-photon emission computed tomography (SPECT) in 22 children with electroclinical features of frontal lobe epilepsy (FLE). Ictal SPECT demonstrated unilateral frontal hyperperfusion in 20 of 22 children (91%) (one lobar, two frontocentral, six dorsolateral, six frontopolar, three orbitofrontal, one medial frontal, and one insula), concordant with electroclinical lateralization in 19 of 20 (95%). Hyperperfusion was evident in the ipsilateral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
105
0
2

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(115 citation statements)
references
References 0 publications
8
105
0
2
Order By: Relevance
“…36 The capability of DTI to localize the epileptogenic zone in suspected FLE is helpful because seizure lateralization can be difficult clinically and on EEG due to the rapid spread of seizure focus in FLE. 37,38 Of the 5 DTI indices, MD demonstrated greater lobar concordance and also greater overlap in all 3 x-, y-, and z-axes with the MEG dipole cluster in patients with MR imaging localization-related epilepsy, similar to the findings in previous studies in adults. [20][21][22] We have found DTI abnormalities occurring both within and also beyond the epileptogenic zone, similar to findings in previous studies.…”
Section: Discussionsupporting
confidence: 83%
“…36 The capability of DTI to localize the epileptogenic zone in suspected FLE is helpful because seizure lateralization can be difficult clinically and on EEG due to the rapid spread of seizure focus in FLE. 37,38 Of the 5 DTI indices, MD demonstrated greater lobar concordance and also greater overlap in all 3 x-, y-, and z-axes with the MEG dipole cluster in patients with MR imaging localization-related epilepsy, similar to the findings in previous studies in adults. [20][21][22] We have found DTI abnormalities occurring both within and also beyond the epileptogenic zone, similar to findings in previous studies.…”
Section: Discussionsupporting
confidence: 83%
“…Although they may be very frequent, they are often brief, and simply too short to be captured by this method. They show a variety of ictal perfusion changes which are distinct from those seen in mesial temporal seizures, and apparently are consistent with the site of origin of the seizure within the frontal lobe, where this is known (23)(24)(25)(26)(27). Hyperperfusion of the basal ganglia, thalamus, and cerebellum seems to be common.…”
Section: Frontal Lobe Seizuressupporting
confidence: 64%
“…Liu et al 30 also found that adult patients with left mesial TLE have significantly reduced regional efficiency in multiple regions in the temporal, frontal, and parietal lobes. We have found more regions of reduced nodal efficiency in the FLE than in the TLE subgroup, which may be due to the rapid spread of seizure activity as a result of the extensive network of connections of the frontal lobe and more frequent seizures in FLE [31][32][33] or, alternatively, an inherently more extensive abnormal regional efficiency from an underlying etiology that predispose to FLE. The more extensive impaired regional networks may be associated with poorer seizure-free surgical outcome in patients with FLE relative to those with TLE.…”
Section: Discussionmentioning
confidence: 76%
“…There were more subnetworks expressing reduced structural connectivity in FLE than in TLE, probably related to the rapid spread of seizure activity and more frequent seizures in FLE. [31][32][33] In both subgroups, the reduced structural connectivity predominantly involved the mesial temporal and frontal basal structures compared with controls. The spread of seizures from the frontal to temporal lobes in FLE and from the temporal to frontal lobes in TLE may have contributed to reduce structural connectivity between the frontal and temporal lobes.…”
Section: Discussionmentioning
confidence: 98%